2014
DOI: 10.1007/s00380-014-0593-5
|View full text |Cite
|
Sign up to set email alerts
|

Circulating matrix metalloproteinase patterns in association with aortic dilatation in bicuspid aortic valve patients with isolated severe aortic stenosis

Abstract: Bicuspid aortic valve (BAV) exhibits a clinical incline toward aortopathy, in which aberrant tensile and shear stress generated by BAV can induce differential expression of matrix metalloproteinases (MMPs) and their endogenous tissue inhibitors (TIMPs). Whether stenotic BAV, which exhibits additional eccentric high-velocity flow jet upon ascending aorta and further worsens circumferential systolic wall shear stress than BAV with echocardiographically normal aortic valve, can lead to unique plasma MMP/TIMP patt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0
1

Year Published

2015
2015
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 41 publications
(37 reference statements)
1
26
0
1
Order By: Relevance
“…In this study, we attempted to shed light on intrinsic defects of the aortic wall leading to the observed similarities by comparing the ascending aortic wall of both diseases with each other and with patients with TAV without MFS. As recently several publications focused on a difference in dilation progress after aortic valve repair dependent on whether the diseased aortic valve was stenotic or regurgitant with concomitant root dilation [ 25 , 26 ]; in the latter, we also paid additional attention to the underlying aortic valve pathology besides structural histopathologic features in the patient groups. In the literature, it is argued that the aortic dilation in the stenotic type is a functional hemodynamic-induced problem, while the aortic wall problem in the root phenotype is genetically determined.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we attempted to shed light on intrinsic defects of the aortic wall leading to the observed similarities by comparing the ascending aortic wall of both diseases with each other and with patients with TAV without MFS. As recently several publications focused on a difference in dilation progress after aortic valve repair dependent on whether the diseased aortic valve was stenotic or regurgitant with concomitant root dilation [ 25 , 26 ]; in the latter, we also paid additional attention to the underlying aortic valve pathology besides structural histopathologic features in the patient groups. In the literature, it is argued that the aortic dilation in the stenotic type is a functional hemodynamic-induced problem, while the aortic wall problem in the root phenotype is genetically determined.…”
Section: Discussionmentioning
confidence: 99%
“…The critical role of MMP-2 as a key molecular mediator was supported by a recent meta-analysis. Wang and colleagues further showed MMP-2 as a circulating biomarker of aortic dilatation in BAV patients(73). Phillippi with Gleason and Vorp at University of Pittsburgh further characterized the medial matrix remodeling of the BAV aorta and found unique patterns as compared to TAV patients(74).…”
Section: Cellular and Molecular Mechanisms Of Bav Aortopathymentioning
confidence: 99%
“…Neither did we find significant relations with aortic dimensions as measured by echocardiography, although a trend was observed for MMP-2 (adjusted p value 0.087). Previous studies have reported altered plasma MMP-2, -9 and TIMP-1 levels in patients with aortic valve stenosis and ascending aorta dilatation, both in bicuspid valves and in chronic thoracic aortic dissection (Ikonomidis et al, 2013;Wang et al, 2016;Zhang et al, 2014). It may therefore be worthwhile to evaluate MMPs in specific patient subgroups with a high risk of aortic dilatation, in combination with more detailed imaging modalities of the aorta, such as CT or MRI.…”
Section: Aortic Stenosis and Dilatationmentioning
confidence: 99%
“…More specific, altered MMP-2, MMP-9 and TIMP-1 levels have been associated with left ventricular (LV) hypertrophy, chronic heart failure and diastolic dysfunction in hypertensive heart disease and coronary artery disease (Ahmed et al, 2006;Chu et al, 2013;Kang et al, 2008;Laviades et al, 1998;Martos et al, 2007). In patients with thoracic aortic aneurysms, specific MMP-2, -9 and TIMP-1 profiles have been described; however, the majority of research in this field is based on histology of the aortic wall rather than circulating blood biomarker levels (Ikonomidis et al, 2013;Wang et al, 2016;Zhang et al, 2014).…”
Section: Introductionmentioning
confidence: 99%